The Influences of The Meccan Education on the Pesantren Tradition with Special Reference to Shaykh 'Abd al-Ḥamīd Kudus - Sunarwoto Sunarwoto (Studia Islamika, 2008)
This article looks at the influence of Meccan education on the pesantren tradition. The author will deal with the rise of Javanese religious scholars in Mecca seen from two interrelated perspectives: textual and intellectual networks. The author will attempt to discuss these indications and link them to the pesantren environment. The author will also shed light on some discourses related to Islamic reforms stimulated by the Javanese ulama (religious scholars) in Mecca and how they influenced the construction of pesantren ideology. The author will end this article with a case study of Shaykh 'Abd al-Hamid Kudus. This study is meant to portray the intellectual career of a Javanese teacher at the Masjid al-Haram in Mecca.DOI: 10.15408/sdi.v15i3.526